Multiplatform management of a Hard Real-Time Ethernet Switch - Pleszko, Aleksander (2012)
The Hard Real-Time Ethernet Switch (HaRTES) allows using the same network to handle multiple traffic flows, without compromising the performance of real-time applications. Furthermore, it also provides flexible and on-line scheduling techniques with admission control capabilities, thus real-time communications flows can be added, removed and updated online with strict temporal isolation. However, HaRTES lacked a standard management interface to configure its parameters and view its status. This paper describes a multiprotocol (SNMP and NETCONF) management interface design, and implementation. It also presents a preliminary validation of the two management technologies.